Analisis Faktor-faktor yang Mempengaruhi Corporate Sustainability - Anggi Adellia; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Corporate Sustainability is part of the company's seriousness in making long-term transformation to maintain the sustainability of stakeholders in the present and in the future. This study aims to determine the effect of green accounting, material flow cost accounting, and green intellectual capital on corporate sustainability. This study uses a quantitative method with an associative approach. The population in this study are all companies listed on the Indonesia Stock Exchange. The sample of this study is basic material sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period which are taken using a purposive sampling technique. This study uses secondary data obtained through the official website of the Indonesia Stock Exchange and related companies. The data analysis method uses multiple linear regression analysis using the SPSS program. The results of the study show that green accounting and green intellectual capital have an effect on corporate sustainability, while material flow cost accounting does not have an effect on corporate sustainability.